The effect of melatonin and carnitine on radiation nephropathy - Ozge Ozdemir; Nilgun Ozbek Okumus; Bilge Gursel; Ahmet Deniz Meydan; Bilge Can Meydan; Oktay Yapici; Sema Yilmaz Rakici (Journal of Radiation and Cancer Research, 2022)
Aims: We aimed to show the protective effect of carnitine and melatonin (MEL) on kidney which were applied before the radiotherapy. Materials and Methods: Seventy-two male Wistar Albino rats were divided six equal groups as Group 1 radiotherapy, Group 2 radiotherapy and MEL, Group 3 radiotherapy and carnitine, Group 4 MEL, Group 5 carnitine, and Group 6 control. Whole abdominal radiotherapy of 10 Gy was applied to the radiotherapy groups. Renal scintigraphy was performed under anesthesia on all rats after a follow-up period of 8 weeks. Histopathologic examination was performed in kidneys. Results: Group 1 showed a statistically significant deterioration of renal scintigraphy function (P < 0.05). Group 2 and Group 3 showed a better function of scintigraphical renal function and there was no significance between the control. There was no damage seen by light microscopy in Group 1, 2, 3. When evaluated histomorphological, there was a significant increase of glomerular width in Group 1 whereas Group 2 and Group 3's glomerular width decreases to the level of control group's (P < 0.00). Conclusion: As a conclusion, we consider that adding carnitine and MEL to the radiotherapy of patients who has a long-expected survival will prevent the complications due to radiotherapy.